Conflitos territoriais envolvendo indígenas e agricultores no norte do Rio Grande do Sul: a trajetória de políticas públicas contraditórias - Kujawa, Henrique Aniceto (Universidade do Vale do Rio dos Sinos, 2014)
This work addresses the ongoing territorial conflicts involving indigenous and familiar farmers in the North of Rio Grande do Sul, understanding them as a result of indigenous territorial policies that have historically promoted the territorialization and reterritorialization of indigenous and farmers as they intend the same land at different times, to indigenous and farmers. The contradictions of these policies promoted a constant struggle, especially during the twentieth century, with greater intensity at the time of demarcation of Indigenous Tents (1910-18), in their reduction and sale of the lands to farmers (1950’s – 1960’s), the reestablishment of the areas historically demarcated (1990’s) and on the ongoing conflicts, configuring a dispute over the territory considered by the indigenous as traditional occupation and the farmers purchased from the State, occupying it for over a century. It is demonstrated that the understanding of the ongoing conflicts requires, on one side, the analysis of the public policies, the way they are constituted on the processes of action and relation of the State and society through their agents, resulting on the specific case on the legitimation or de-legitimation of the indigenous territorial right and / or of the farmers. The constitution of 1988 guarantees the demarcation of the lands the Indigenous peoples traditionally occupy. However, there are different interpretations left about the scope of the concept of traditional occupation, embracing the prospect of indigenatus and immemorial occupation or requiring the indigenous presence in the territory at the time of enactment of the Magna Carta. It is on the institutional acting of the State and on the relation and shock with the different social sectors that the agenda of this public policy is being constituted and reconstituted. It has already advanced on the recognition that, beyond the indigenous necessity for new lands, the rights of the farmers must be recognized. On the other hand, there is the need to understand the reasons for the outbreak and the intensification of the conflicts from indigenous territorial demands, their historical condition, result of a century of interethnic friction. In that sense, the concept of emergent diversity becomes elucidatory, contributing for the realization of the Indigenous peoples, their needs, their strategies to extend the demarcation of the territories from their current condition. The interethnic friction and the ethnogenesis constituted and indian, mainly the kaingan, inserted, even if subalternally, to the consumer market, altering significantly their relation with land and production; thus, the demarcation of new indigenous lands does not necessarily lead them to reestablish relations of subsistence and integration with nature, characteristics of past centuries. It is of utmost importance the utilization of the perspective of ethnodevelopment which contributes to the recognition of both the Indigenous peoples and the farmers, enabling the lead role on the definition of the needs and on the building of the public policies which aim to achieve their rights. These features were used, methodologically: secondary sources, which consist of bibliographic research related to the theme, as well as the use of the administrative processes of identification, delineation and demarcation of the indigenous lands in which lie the Anthropological Reports and territorial reports; and primary sources, which consist of interviews with farmers, indigenous peoples and organizations supporting each of these social groups.
Keywords: Agricultores; Conflito social; Etnodesenvolvimento; Fricção interétnica; Indígenas; Política territorial; Social conflict; Ethnodevelopment; Interethnical friction; Indigenous peoples; Territorial policy; ACCNPQ::Ciências Humanas::Sociologia